2008
DOI: 10.1111/j.1525-1438.2007.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous primary cancers of the endometrium and ovary

Abstract: Simultaneous detection of malignancy in the endometrium and ovary represents an uncommon event. The objective of the study was to clarify the possible factors that influenced on the survival. From 1977 to 2005, totally 27 patients fulfilled the criteria and were included in the study. The medical records and the pathologic reports were reviewed. The histologic determination was followed by the World Health Organization Committee classification, and cancer stage was based on the staging system of the FIGO. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 17 publications
5
97
1
Order By: Relevance
“…The median follow-up period (95 months) was sufficient to examine disease-free survival. Many studies have postulated that the survival rate of patients with SEOC is better than that of patients with EOC [4,17,18]. However, this study does not support this finding; following adjustment for histological type and stage, the prognosis was not remarkably different between SEOC and EOC in the early stages.…”
Section: Discussioncontrasting
confidence: 79%
“…The median follow-up period (95 months) was sufficient to examine disease-free survival. Many studies have postulated that the survival rate of patients with SEOC is better than that of patients with EOC [4,17,18]. However, this study does not support this finding; following adjustment for histological type and stage, the prognosis was not remarkably different between SEOC and EOC in the early stages.…”
Section: Discussioncontrasting
confidence: 79%
“…The scope of general surgery included hysterectomy, bilateral salpingo-oophorectomy, omentectomy and appendectomy. Pelvic lymph node dissection depended on the pathological findings (9,10). The treatment of patients with ovarian cancer is generally based on chemotherapy with paclitaxel plus cisplatin (TP) regimen or cisplatin + doxorubicin + cyclophosphamide (PAC) regimen and the length of treatment ranges from 2 to 10 cycles, generally 3 to 6 cycles; however, patients with stage Ⅰ or II grade 1 ovarian cancer do not require chemotherapy.…”
mentioning
confidence: 99%
“…In a study done by Y Chiang et al done on 23 cases of synchronous ovarian and endometrial tumours 63% showed similar histology [5] . A 10 year study done by Young Kuei Lim et al on 75 patients with synchronous tumours showed 73.9% being endometrioid endometrial cancers and 26.1 % with tumours of different histological type [6] .…”
Section: Discussionmentioning
confidence: 99%